Insurance with telematics as an insurance market driver: regulation and prospects - A. V. Romanova; S. Yu. Shchukin; S. V. Chelokidi; N. E. Spirina (Вестник университета)
Currently, the insurance market is actively using modern technologies, which allows companies to compete with each other and attract customers. However, the possibilities of introducing artificial intelligence and big data (AI and DB) into the regulated sphere, which is insurance, are usually limited compared to unregulated sectors. The purpose of the study is to substantiate the need and develop measures to regulate the use of AI in insurance, in general, and auto insurance, in particular, as well as to determine the prospects and risks of the spread of the use of AI technologies in insurance. The research used scientific works of domestic and foreign scientists in the field of AI and DB development in insurance, regulatory legal acts and program and strategic documents for the development of the Russian insurance market, as well as data generated by the authors on the basis of official statistical materials. For analytical data processing, the method of statistical analysis, the system-logical method, as well as such general scientific methods as induction, deduction and synthesis are used. The slowdown in the growth rate of the insurance market at the present time is due to both the tightening of the regulator’s requirements for the financial stability of insurers, and the lack of prospects for development, the complexity of the introduction of AI and DB in insurance. A competent state approach to regulating the activities of subjects in the topic under consideration entails a number of benefits and advantages, will allow to neutralize or reduce the influence of the identified constraining factors.